1993
DOI: 10.3382/ps.0720042
|View full text |Cite
|
Sign up to set email alerts
|

Daily Energy Allotment and Reproductive Performance of Broiler Breeder Males

Abstract: Ross broiler breeder males, housed in floor pens with females and fed from separate feeders, were given 125 g/day of isonitrogenous diets formulated to provide 300,340, and 380 kcal per male per day between 28 and 60 wk of age. Males given 300 kcal/day maintained their initial BW and were consistently lighter than those fed the two higher energy levels; BW of males given the two higher energy allotments did not differ from each other. Fertility levels, over the whole experiment, averaged 80.1, 91.1, and 83.0% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
2
9
1
Order By: Relevance
“…Similarly in Experiment 2, 3.6-kg cage-housed males fed 280 kcal ME/d lost weight in the first 4 wk when daily low ambient temperatures averaged 15.2 C and highs averaged 21.0 C, suggesting that the maintenance energy requirement under these conditions is greater than 280 but less than 320 kcal ME/d. These data are in basic agreement with those of McCartney (1983, 1986) and Attia et al (1993), showing maintenance energy requirements of broiler breeder males to fall into a range of 81 to 95 kcal ME/kg BW per d. Sexton et al (1989) reported that the 192 kcal ME/d would support a minimal amount of growth in caged broiler breeder males weighing about 3.4 kg at the onset of the experiment. This value suggests that 55 to 56 kcal ME/kg BW slightly exceeds the energy maintenance requirements; a value markedly lower than those found by other workers.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similarly in Experiment 2, 3.6-kg cage-housed males fed 280 kcal ME/d lost weight in the first 4 wk when daily low ambient temperatures averaged 15.2 C and highs averaged 21.0 C, suggesting that the maintenance energy requirement under these conditions is greater than 280 but less than 320 kcal ME/d. These data are in basic agreement with those of McCartney (1983, 1986) and Attia et al (1993), showing maintenance energy requirements of broiler breeder males to fall into a range of 81 to 95 kcal ME/kg BW per d. Sexton et al (1989) reported that the 192 kcal ME/d would support a minimal amount of growth in caged broiler breeder males weighing about 3.4 kg at the onset of the experiment. This value suggests that 55 to 56 kcal ME/kg BW slightly exceeds the energy maintenance requirements; a value markedly lower than those found by other workers.…”
Section: Discussionsupporting
confidence: 89%
“…These findings agree with those of Attia et al (1993) but are in contrast to the report of Sexton et al (1989), who found an increase in carcass fat associated with increased energy intake of caged males.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…At the beginning of the experiment (at one day of age), the chicks were individually weighed to the nearest gram, then they were weighed weekly till the end of the experiment according to (Attia, 1995).…”
Section: A Body Weight (Bw)mentioning
confidence: 99%
“…Extensive studies suggested that offspring performance could be influenced by maternal nutritional status at specific periods (Enting et al 2007;Zhu et al 2012;Koppenol et al 2015). Maternal diets with high energy levels increased the body weight of male offspring and the number of eggs per hen (Attia et al 1993(Attia et al , 1995b. High energy allotments for male broilers increased body weight of 42-d-old offspring (Attia et al 1995a).…”
Section: Introductionmentioning
confidence: 99%